2021
DOI: 10.4314/as.v20i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four organic amendments on soil physiochemical properties and yield of maize (Zea mays) and cowpea (Vigna unguiculata) intercrop in Awka, southeastern Nigeria

Abstract: Effects of four organic amendments on some soil physical and chemical properties were investigated in Awka, Anambra State in southeastern Nigeria. Over the years, use of synthetic materials in crop production has been a common practice globally. The attendant detrimental effects of the chemicals used in the formulation of these synthetics on animal and human health as well as the environment has made researchers to look out for a better agronomic practice that would not only improve productivity but at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The higher value of vegetative characteristics of legume and maize intercrop may possibly be attributing to less weed competition, since the majority of the land is covered by crops that inhibit weed growth. This result was also supported by Onunwa et al [29] where they stated that organic manure resulted in higher number of leaves for maize and cowpea. Similar findings were reported by Okpanachi et al [30].…”
Section: Number Of Leavessupporting
confidence: 72%
“…The higher value of vegetative characteristics of legume and maize intercrop may possibly be attributing to less weed competition, since the majority of the land is covered by crops that inhibit weed growth. This result was also supported by Onunwa et al [29] where they stated that organic manure resulted in higher number of leaves for maize and cowpea. Similar findings were reported by Okpanachi et al [30].…”
Section: Number Of Leavessupporting
confidence: 72%
“…The application of chicken manure organic fertilizer significantly increased the content of SOM, SON, AP, S-NR, S-HR, S-UE, S-ACPT, and S-β-GC. Previous studies examining the effects of manure fertilizer application have shown that animal manure helps increase biological activity and soil fertility, improve soil physical and chemical properties (Adebola et al 2017 , Onunwa et al 2021 ), and promote the release of soil nutrients and the activity of soil enzymes (Adubasim et al 2018 , Ogumba et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the inorganic mulch proved more effective in conserving soil moisture than the organic mulch. In research conducted by Onunwa et al (2023), the impact of various mulch types on soil water utilisation and okra yield was examined. The findings revealed that both mulch varieties notably enhanced soil moisture levels and positively influenced yield compared to the control treatment.…”
Section: Effect Of Mulch On Soil Residual Moisture Conservation At Di...mentioning
confidence: 99%